Strategic Approaches and Institutional Tools of the Shanghai Cooperation Organization in Resolving Iran’s Security Concerns - Tairova, Diana (Ampera: A Research Journal on Politics and Islamic Civilization, 2025)
In the context of increasing global interdependence and regional integration, Iran’s security challenges and strategic imperatives must be analyzed through the lens of multilateral frameworks such as the Shanghai Cooperation Organization (SCO). This paper examines the implications of Iran’s transition from observer status to full membership in the SCO, highlighting the geopolitical, economic, and security ramifications of this shift. Iran's accession represents a significant geopolitical achievement that enhances its positioning within Eurasia and counters narratives of international isolation promoted by Western powers. The study explores key benefits for both Iran and the SCO, including enhanced energy cooperation, expanded economic connectivity, and strengthened regional security mechanisms, particularly regarding the Afghan crisis and the fight against terrorism. Iran's strategic orientation toward the East—articulated by its leadership—aligns with the SCO's broader objective of promoting a multipolar world order independent of Western hegemony. Furthermore, Iran’s integration into transnational infrastructure projects and its role in regional trade corridors such as the North-South Transport Corridor and China's Belt and Road Initiative amplify its strategic value within the organization. The paper also assesses the potential tensions with pro-Western Gulf monarchies and the strategic balancing required to mitigate intra-regional frictions. Ultimately, Iran’s SCO membership may serve as a catalyst for deepening regional integration across Eurasia and contribute to the emergence of a “fourth pole” in the global order. The study employs scenario-based analysis and case study methods to forecast the trajectory of Iran-SCO relations and assess the organization’s capacity to absorb Iran’s strategic weight while addressing collective security challenges.